Boys and Inclusion in Education in the Caribbean: A Jamaican Case Study - Clarke, Christopher (UNESCO, 2019)
This study is part of a series of webinars (GEM Report 2020 Latin America and the Caribbean: Inclusion and Education) titled ‘Boys and Inclusion in Education in the Caribbean: A Jamaican Case Study’. It provides statistics on population as well as percentage of national budget for education. The case study participants were: (i) Four Principals (primary, secondary, rural, urban, male, female); (ii) Three Education Administrators; (iii) Three teachers; (iv) Three Dropouts; (v) Two Community members
Ciclo de webinars. Informe GEM 2020 America Latina y el Caribe: Inclusion y educacion